Advances in synaptic PET imaging and intervention with synapse-targeted small-molecular drugs for dementia diagnosis and therapy - Xiuhong Lu; Bin Ji; Gang Huang; Hong Ding (Fundamental Research)
Dementia is characterized by synaptic and neuronal dysfunction in disease-specific brain regions. Repeated failure of dementia clinical trials with therapeutic drugs targeting abnormal protein aggregates has caused researchers to shift their focus to synaptic functions and increased the importance of clinically available imaging for synaptic density and the development of synapse-targeted intervention. Synaptic density imaging with positron emission tomography (PET) tracer enables non-invasive detection of synaptic loss and hence investigates the association with other neuropathological events exemplified by disease-specific abnormal protein accumulation. Many studies have reviewed the progress of synaptic density imaging; however, to our knowledge, there is no article yet that summarizes the research progress of multimodal imaging of synaptic density tracers combined with other dementia biomarkers. Moreover, synaptic function intervention for dementia therapy has not yet been summarized. In this review, first we detail the progress of synaptic density imaging including tracer development and preclinical/clinical application, followed by a discussion of multimodal imaging of synaptic density tracers combined with classic dementia biomarkers in the clinical research stage. Finally, we briefly summarize the synapse-targeted drugs for dementia therapy.